Effects of physical exercise on functional capacity in hemodialysis patients. A systematic review (2022)
The aim of this study was to conduct a systematic review in order to evaluate the main effects of intradialytic physical exercise on different parameters of functional capacity in dialytic patients. The clinical question that guided the objective of this study was developed using the PICO method (Population, Intervention, Comparation and Outcome)." Where i) population: patients on hemodialysis; ii) intervention: physical exercise; iii) comparison: active vs sedentary patients; and iv) outcome: functional capacity. The combinations of the following keywords were used: CKD, physical exercise, exercise, physical training and hemodialysis. The selection of studies was performed using the PubMed database and only studies dating from 2011 to 2021 were selected. The search results led to 53 studies. The following steps were carefully analyzed, such as the title, abstract and the full paper description to evaluate whether they met the following inclusion criteria: i) target audience of the studies should be patients on hemodialysis; ii) outcomes that analyze different parameters of functional capacity; iii) Intervention using physical exercise; and iii) intradialytic exercise. The final results indicate that intradialytic physical exercise can cause significant changes in the evaluated outcomes of functional capacity, such as increased strength, improvement of cardiorespiratory function, and improvement of locomotor activity. It was concluded that intradialytic training protocols should be encouraged in clinical practices because they are responsible for causing beneficial changes in the functional capacity of hemodialytic patients.